PEMBERDAYAAN PEMUDA RT.09 RW. 04 DI KELURAHAN TUNJUNG SEKAR MELALUI PENDIDIKAN DAN PELATIHAN PEMBUATAN RANGKA TEROP - Sadar Wahjudi; Kasijanto Kasijanto; Listiyono Listiyono; Eko Hendry Suyono; Moh Nasir Hariyanto (Publisher UPT P2M Politeknik Negeri Malang, 2017)
In neighborhood RT.09 RW.04 Tunjungsekar urban village, many young people are unemployed and have high motivation in restricting their village in RT environment, besides because in neighborhood RT. this is a lot of activities and there is no suitable place in the preparation of the current event or is being done on the road by installing tents from the rental of a large enough cost and hi cash RT. From the above problems and initial surveillance from the authors agreed to be given training and education of Electrical Electrical to make the framework of the terop on the youth in neighborhood RT.09 RW.4 in Tunjungsekar Village to be used as the provision of his life. The purpose of this PKM is: 1. Helping the youth in neighborhood RT.09 RW.04 to get Electrical Laser skill, 2.Helping youth in neighborhood RT.09 RW.04 in making frem of tend, which many use electric welding machine , 3. Helping youths in neighborhood RT.09 RW.04 to gain knowledge in work with Electrical Welding machine so that it will improve their competitiveness and income. The results obtained in this PKM is 1. the presence of awning in the neighborhood RT.09 RW.04 Tunjungsekar Village, which can be used alone or rented so that it can raise the cash RT. 2. The youth have welding skills so as to be able to increase their income. and 3. Youth groups in the environment has a welding machine from donation Polytechnic of Malang.